Consumindo Lady Gaga: os little monsters e a construção de identidades de gênero - Corrêa, Luiza Betat (2019)
The research addresses the consumption of celebrities and construction of gender identity, with the purpose of analyzing the uses and appropriations that Little Monster fandom makes of Lady Gaga’s life and work, in particular aspects related to body and sexuality, for the construction of gender identities. The research problem seeks to answer how the media, mercantile and cultural logics are related to the processes of distinction and integration in the formation of gender identities of the fans. The mobilized theories are distributed in four axes, focused, on Latin American consumer studies, celebrities research, fan and identities and gender studies. Methodologically, we used an ethnographic approach on the Internet in three groups and a fanpage of the online social network Facebook, through the combination of two perspectives, Ethnography for the Internet (HINE, 2015a, 2015b, 2016) and Netnography (KOZINETS, 2014) , and we operated a bibliographic and documentary research regarding the Lady Gaga’s career. The analyses were conducted and supported in two categories, body and sexuality. They present, referring to the first, that the singer's consumption is associated with the reception of physical characteristics that escape the socially perpetuated pattern and the management of insecurities associated to that scope, however, the senses elaborated by the fans are based more on the speech and the visual constructed by the singer, which are complemented by the image of her physical body, since this being, for the most part, is within the ideals of beauty. In what corresponds to sexuality, Lady Gaga symbolizes the acceptance and understanding of LGBT+ individuals’ sexualities and the encouragement for the experience of sexual freedom. Although, it is observed that the movements described are, in primacy, articulated to the initial phase of her career, which means, the period in which the fans most identify with what was produced by the artist, once we learn that this is the moment when the media, mercantile and cultural logics were better harmonized. Nowadays, there is a certain disidentification between the demands of fans and what is endorsed by Lady Gaga.